Implementation of Docker Swarm on A Mariadb Database Clustered with Galera Clusters on More than One Host (Multi Host) - Damhuri*, Rifqy Adli; Widodo, Suryarini (Universitas Syiah Kuala, 2023)
The Covid-19 pandemic in Indonesia, which began in 2019, has had an impact on all levels of society. With this pandemic occurring, the Indonesian government made several policies with the aim of stopping the spread of the Covid-19 virus. One form of policy that is carried out is by imposing a system of Imposing Restrictions on Community Activities (PPKM), to prevent the spread of the virus through physical contact. The existence of this PPKM is one of the drivers of digitization in almost all sectors. This transformation in the digital world must be facilitated with qualified infrastructure. One example of important infrastructure needed to support digital transformation is a server and to be specific is a database server. To improve and optimize the performance of the server, system development is carried out using docker swarm on a mariadb database clustered with galera clusters on more than one host (multi host) that can be done by installing ubuntu and docker, swarm initialization, create overlay network, pull galera image, create cluster service, Prometheus and grafana installation and configuration, test integeration on database, and monitoring server. All cpu usage percentage from monitoring results show the percentage not reach 100% which means there are no overload and overworked.